Developmental Co-expression of Vglut2 and Nurr1 in a Mes-Di-Encephalic Continuum Preceeds Dopamine and Glutamate Neuron Specification - Dumas, Sylvie; Wallén-Mackenzie, Åsa (Frontiers in Cell and Developmental Biology, 2019)
Midbrain dopamine neurons exist as several subtypes and are found in a heterogeneous environment intermingled with glutamatergic, GABAergic and co-releasing neurons. The developmental programs underlying this heterogeneity have remained elusive. Here, combinatorial gene expression analysis was performed at stages when neuronal phenotypes are first specified. Histological data from embryonal day (E)9.5-14.5 in the mouse demonstrate that most early differentiating dopamine neurons express the gene encoding the Vesicular glutamate transporter 2 (VGLUT2) before onset of any dopaminergic markers. Further, prior to its down-regulation in maturing dopamine neurons, Vglut2 mRNA co-localizes extensively with Tyrosine hydroxylase (Th) and Nurr1, commonly used as markers for midbrain dopamine neurons. Beyond dopamine neurons, Vglut2 and Nurr1 show substantial overlap in neurons that maintain a glutamatergic phenotype along a mes-di-encephalic continuum. The results suggest that Vglut2/Nurr1-double positive cells give rise both to dopaminergic and glutamatergic neurons. Further, developmental analysis of markers representing dopamine neuron subtypes, including the newly described NeuroD6 subtype, identify early subtype specification. This study contributes to the developmental decoding of the recently discovered heterogeneity among neurons residing along the mesencephalic flexure.